PERBANDINGAN KEMAMPUAN MEMBACA PERMULAAN ANTARA METODE SUKU KATA DENGAN METODE EJA BERBANTUAN MEDIA KARTU KATA - Rismawati Rismawati; Kadek Dewi Wahyuni Andari; Kartini Kartini (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
This study aims to determine differences in student’s initial reading skills by Applying the Syllable Method aided and Spell Method by Word Card Media for Class II at SDN 024 Tarakan. The type of this research is quasi-experimental research. This research was conducted in August 2019. With a population of class II of SDN 024 Tarakan and the sample consisted of two classes, namely class II D as an experimental class and class II C as a control class. The technique in taking the sample used is Random Sampling. The research data were processed with the help of SPSS V.21 for Windows Software. The results showed that there were no differences in the results of the ability to read the beginning by applying the Syllabic Method and Spell Method Assisted Media Media Card Word. The results of the Independent Sample T-teston student’s initial reading ability were obtained tcount= 0.045 at the significance level of 0.05 and df = 53, obtained ttable= 2.01 means tcount ≤ ttable.